Varying effects of recommended treatments for heart failure with reduced ejection fraction: meta‐analysis of randomized controlled trials in the ESC and ACCF/AHA guidelines. (4th July 2016) - Thomsen, Marius Mark; Lewinter, Christian; Køber, Lars
Abstract: The aim of this paper is to evaluate the treatment effects of recommended drugs and devices on key clinical outcomes for patients with heart failure with reduced ejection fraction (HFREF). Randomized controlled trials (RCTs) listed in the 2012 HF guideline from the European Society of Cardiology as well as the 2013 HF guideline from the American College of Cardiology Foundation and American Heart Association were evaluated for use in the meta‐analysis. RCTs written in English evaluating recommended drugs and devices for the treatment of patients with HFREF were included. Meta‐analyses, based on the outcomes of all‐cause mortality and hospitalization because of HF, were performed with relative risk ratio as the effect size. In the identified 47 RCTs, patients were on average 63 years old and 22% were female. Drugs targeting the renin‐angiotensin‐aldosterone system, beta‐blockers, cardiac resynchronization therapy (CRT), and intracardiac defibrillator devices (ICDs) significantly reduced the risk of death with reductions of 14–19, 23, 20, and 20%, respectively. Drugs targeting the renin‐angiotensin‐aldosterone system, beta‐blockers, digoxin, and CRT significantly reduced the risk of HF hospitalization with reductions of 24–37, 22, 60, and 36%, respectively, while ICDs significantly increased the risk with 34%. Ivabradine showed no significant effects on either outcome. As such, the majority of recommended HFREF treatments offered significant treatment benefits. However, many of the included studies were from the 1990s or earlier, and one must therefore be cautious when extrapolating these results to contemporary patients with HF.